‘Special Witness’ in Criminal Proceedings - Kuconis, Pranas (Teisė, 2023)
The article discusses the reasons and history of the creation of the norms that established the institute of the ‘special witness’, analyzes the content of this institute, identifies some problems of legal regulation and its application and proposes ways to solve them.